Rebranding As a Tool for Innovation and Recovery of a Company Brand - Zuzana ROSNEROVA; Eva KICOVA; Olga PONISCIAKOVA; David VRTANA (Communications of International Proceedings, 2023)
The development and growth of successful companies in the market is conditioned by the strategies that the company implements in order to be able to achieve its successful operation in the market in the future. The current market environment is marked by rapid development, which has to a large extent conditioned the globalization process, which brings with it new challenges and determines new market conditions. For this reason, in an effort to revive their operations and report better results, companies are implementing changes in marketing concepts. One such step is to change the brand, called "rebranding." Rebranding is the process of examining, reassessing and replicating brands that are located in companies for the growth of competitiveness goals. Rebranding can be considered an innovative tool of the corporate brand that can be used as a strategy for the success of the marketing strategy for the next period. The paper describes the basic terminology of the issue, identifies rebranding as a key aspect of integrated marketing communication, and describes the basic aspects of the corporate brand. The aim of the paper is to identify the reasons for the change of the corporate brand, which manifested itself in the case of the logos of world-famous companies in the past year 2021, and to specify the differences that occurred in their brands.
Keywords: brand; rebranding; logo; globalization; integrated marketing communication